Synthesis of model DNA and their application as substrates of nucleotide excision repair - Evdokimov, A.N.; Tsidulko, A.Yu.; Petruseva, I.O.; Koroleva, L.S.; Serpokrylova, I.Yu.; Silnikov, V.N.; Lavrik, O.I. (Вiopolymers and Cell, 2012)
Aim. Nucleotide excision repair (NER) is DNA repair system responsible to remove bulky lesions from DNA. These lesions appear in DNA as consequence of UV-light irradiation or environmental stress. Study of NER is extremely important to improve action of chemotherapeutic drugs. Methods. In vitro NER-assay and photoaffinity modification were used. Results. Long linear DNA analogs mimicking NER substrates have been synthesized. DNA analogs are 137-mer duplexes containing in their internal positions nucleotides with bulky substitutes imitating lesions with fluorochloroazidopyridyl and fluorescein groups introduced using spacer fragments at the 4N and 5C positions of dCMP and dUMP (Fap-dC- and Flu-dU-DNA) and DNA containing a (+)-cis-stereoisomer of benzo[a]pyrene-N2-deoxyguanosine (BP-dG-DNA). The interaction of the modified DNA duplexes with the proteins of NER-competent HeLa extract was investigated. The substrate properties of the model DNA in the reaction ofspecific excision were shown to vary in the row Fap-dC-DNA << Flu-dU-DNA < BP-dG-DNA. Conclusions. In vitro assay show that DNA analogs represent an interesting tool for the estimation of cellular repair activities. The developed approach should be of general use forthe incorporation of NER-sensitive distortions into model DNA and seems to be very promising for repair mechanism studies. Keywords: nucleotide excision repair, model bulky substituted DNA substrates. Мета. Ексцизійна репарація нуклеотидів (NER) – це система репарації ДНК, відповідальна за видалення об’ємних пошкоджень зі складу ДНК. Такі пошкодження можуть виникати за впливу як опромінення ультрафіолетом, так і факторів довкілля. Вивчення системи NER є вкрай важливим для підвищення ефективності хіміотерапевтичних препаратів. Методи. Використано реакцію NER in vitro та фотоафінну модификацію. Результати. Синтезовано довгі лінійні ДНК, які імітують субстрати NER, що являють собою 137-мірні ДНК-дуплекси і містять у внутрішніх положеннях ланцюгів нуклеотиди із введеними за допомогою спейсерних фрагментів по 4N- і 5C-положеннях dC і dU фторхлоразидопіридильною і флуоресцеїновою групами (Fap-dC- і Flu-dU- ДНК), а такожДНК, яка вміщує (+)-цис-стереоізомер бензо[a]пі рен-N2- дезоксигуанозину. Досліджено взаємодію модифікованих ДНК-дуплексів з білками NER-компетентного екстракту клітин HeLa. Показано, що субстратні властивості модельних ДНК у реакції специфічної ексцизії змінюються в ряду Fap-dC-ДНК << Flu-dU-ДНК < BP-dG-ДНК. Висновки. Дослідженнями in vitro встановлено, що ДНК-аналоги є важливим інструментом для оцінки клітинної репарації. Розроблений підхід виявився універсальним для включення до складу ДНК пошкоджень, які упізнаються системою NER, а також досить перспективним для вивчення механізмів репарації. Ключові слова: ексцизійна репарація нуклеотидів, модельні ДНК-субстрати. Цель. Эксцизионная репарация нуклеотидов (NER) – это система репарации ДНК, отвечающая за удаление объемных повреждений из состава ДНК. Такие повреждения могут появляться под воздействием как облучения ультрафиолетом, так и факторов окружающей среды. Изучение системы NER крайне важно для повышения эффективности химиотерапевтических препаратов. Методы. Использованы реакция NER in vitro и фотоаффинная модификаця. Результаты. Синтезированы протяженные линейные ДНК, имитирующие субстраты NER, которые представляют собой 137-мерные ДНК-дуплексы, содержащие во внутренних положениях цепей нуклеотиды с введенными с помощью спейсерных фрагментов по 4N- и 5C-положениям dC и dU фторхлоразидопиридильной и флуоресцеиновой группировками (Fap-dC- и Flu-dU- ДНК), а также ДНК, включающая (+)-цис-стереоизомер бензо[a]пирен-N2-дезоксигуанозина. Исследовано взаимодействие модифицированных ДНК-дуплексов с белками NER-компетентно го экстракта клеток HeLa. Показано, что субстратные свойства модельных ДНК в реакции специфической эксцизии меняются в ряду Fap-dC-ДНК << Flu-dU-ДНК < BP-dG-ДНК. Выводы. Исследованиями in vitro установлено, что ДНК- аналоги являются важным инструментом для оценки клеточной репарации. Разработанный подход оказался универсальным для включения в состав ДНК повреждений, узнаваемых системой NER, а также достаточно перспективным для изучения механизмов репарации. Ключевые слова: эксцизионная репарация нуклеотидов, модельные ДНК-субстраты.